2006
DOI: 10.1093/toxsci/kfl003
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Multiple Mitogen-Activated Protein Kinases in Pro/Pre–B Cells by GW7845, a Peroxisome Proliferator–Activated Receptor γ Agonist, and Their Contribution to GW7845-Induced Apoptosis

Abstract: There is growing interest in using peroxisome proliferator-activated receptor (PPAR) gamma agonists as chemotherapeutic agents in hematologic malignancies. PPARgamma agonists of diverse chemical structure induce apoptosis in several malignant B cell lines. However, PPARgamma agonists also induce apoptosis in normal B cells. One such agonist, GW7845, rapidly induces apoptosis in early B cells. Understanding the mechanisms of PPARgamma agonist-induced death is essential to minimizing loss of normal cells during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…PPAR γ ligands have been shown to induce the activation of p38 MAPK in different cell systems [16, 17]. In line with this, we showed that rosiglitazone increased the phosphorylation of p38 MAPK in NSCLC cells.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…PPAR γ ligands have been shown to induce the activation of p38 MAPK in different cell systems [16, 17]. In line with this, we showed that rosiglitazone increased the phosphorylation of p38 MAPK in NSCLC cells.…”
Section: Discussionsupporting
confidence: 88%
“…PPAR γ ligands have been shown to induce the activation of p38 MAPK in different cell systems [16, 17]. Activation of p38 mitogen-activated protein kinase (MAPK) and its downstream kinase MK2 have been associated with the phosphorylation of TSC2 [18].…”
Section: Resultsmentioning
confidence: 99%
“…SP6 is a specific and potent catalytic inhibitor of JNK that has been widely employed to determine the contribution of the JNK pathway to apoptosis induced by numerous agents in a variety of cell types. It has been particularly useful in elucidating the role of the JNK pathway in the induction of apoptosis in primary cell cultures and established cell lines of B-lymphoid lineage cells (Bloom et al, 2006;Schlezinger et al, 2006). Both arsenite and vincristine induced apoptosis in EW36 B-cells in a concentration dependent manner (Figure 2; A and B, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…MAPK cascade transducer signals from the cell surface change the gene expression that controls diverse functions such as the inflammatory response of epithelial cells (38), proliferation, differentiation, transformation and apoptosis (39). In particular, p38 MAPK is a key modulator of several target genes that ultimately control infiltration of monocytic cells, acute intestinal inflammation and intestinal electrolyte and water secretion, and in response to a variety of stimuli regulates cytokine production (40).…”
Section: Discussionmentioning
confidence: 99%